Saúde Mental em Tempos de Pandemia: um Programa de Comunicação Interna de Atenção à Saúde do Servidor da Universidade Federal de Goiás (Intercom - Brazilian Journal of Communication Sciences, 2024)
In conjunction with emergency public health actions to control the new coronavirus pandemic, there are several efforts to reduce the negative impact on workers' mental health. The objective of the research is to understand if there is an impact relationship between the Covid-19 pandemic and the mental health of the servers of the Federal University of Goiás. Through the case study, a descriptive analysis, frequency distribution and correspondence analysis were performed using the Sphinx® system, for variables with the same categories of secondary data responses, from an institutional survey carried out by UFG. The study shows that there is an impact relationship between the Covid-19 pandemic and the mental health of servers, in addition, the work regime, which placed most servers in remote work, was a catalyst for mental disorders such as anxiety. , depression and others. Communication presents itself as a problem and some groups of servers felt the impact at a higher level such as the elderly, professionals who have children, especially female individuals, and outsourced workers. Finally, an internal communication program for the health care of the UFG server is presented.